Associations Between Covid-19 Effects and Companies’ Strategic Responses - Aldemy de Souza Silva; Paulo Cesar Bontempo; Bento Alves Costa Filho (Journal of Management Research, 2024)
This article aims to identify associations between the effects of the exogenous shock caused by the Covid-19 pandemic on companies and the strategic responses adopted. Quantitative research was carried out, having been used as data collection technique, a survey with the 431 supplier companies of the Federal University of Goias - Brazil in 2020. A questionnaire with closed questions was sent by e-mail to all suppliers, made available via link to Google Forms Plataform. The interpretation of strategic responses to the shock caused by the pandemic in the light of the behavioral theory of firm allowed to conclude that the concept of organizational slack is useful for understanding the associations found between the effects of the pandemic on companies and the strategic answers. By performing a multiple correspondence analysis, it was possible to verify the formation of three distinct groups involving categories of pandemic effects and strategic responses of companies. The association between the negative effects of the pandemic and strategic response of retrenchment can be interpreted as the search for a solution to a deterioration of the organizational slack. The association between the positive effects of the pandemic and the strategic response to innovation illustrates the role played by the organizational slack, allowing flexibility in the face of uncertainty.